Editorial highlights for Lavai-International Journal of Education - Onolragchaa Ganbold; Dulamsuren Jambaldorj (Lavai)
Publishing and developing quality of scientific journals is always challenging. We have been published the first issue of Lavai – International journal of Education in 2003 (all articles in Mongolian), and it is still growing continuously. Because, it’s the first editorial note ever, we would highlight several milestones in history of Lavai – International journal of Education from our past. First, we received both pISSN 2410-4507 and eISSN 2959-9334 in 2015 and 2022 respectively. Secondly, we successfully hosted by the Mongolian Journal Online by December 2022. Simultaneously, we also recognized as international journal that indexed in Google Scholar, Dimensions and EBSCO with unique DOI numbers for each publishing article. Third, we publish only articles in English since 2024 (Vol. 20 No.31). Consequently, we hopefully believe that range of audience of our journal will increase. Fourth, we redesigned our publishing article format since Vol. 20, No. 30 (2024), which is more attractive than previous format. Lastly, we successfully indexed in Directory of Open Access Journals by March of 2025. Therefore, all published articles of this journal are included in the indexing and abstracting coverage of Google Scholar, Dimensions, EBSCO and DOAJ.